Fair-faced concrete and preparation method thereof
By introducing modified carbon nanotubes and other components into clean water concrete, forming a hydrophobic barrier and composite structure, the problem of insufficient waterproof performance of traditional clean water concrete is solved, significantly improving the permeability and compressive strength, and improving the overall performance and aesthetics of the concrete.
Patent Information
- Application Number
- CN202411769988.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-18
AI Technical Summary
Traditional clean water concrete has shortcomings in waterproof performance, resulting in deterioration and damage to the concrete structure.
Modified carbon nanotubes modified from alkoxysilane emulsion are used to combine resin materials, polyamideimide and other components to form a dense hydrophobic barrier and composite structure to improve the permeability and compressive strength of concrete.
It significantly improves the permeability and compressive strength of clean water concrete, forms a surface layer with hydrophobic properties, and enhances the overall strength and aesthetics of the concrete.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and more specifically, to a kind of fair-faced concrete and a preparation method thereof. Background Art
[0002] In recent years, with the continuous development of social economy, fair-faced concrete structures have become more and more popular due to their natural and simple unique beauty. The so-called fair-faced concrete refers to the building without any decoration on the exterior, which is formed in one step by using the cast-in-place process, and no external plastering is performed after the casting formwork is removed. The plain surface after the concrete casting is directly used as the finishing surface, achieving the effect of "solid inside and beautiful outside" through its own texture.
[0003] In the related art, the preparation of plain concrete mainly depends on raw materials such as cement, aggregate, water and appropriate amount of admixtures. These raw materials are mixed, stirred, formed and cured to form a concrete structure with certain strength and durability. However, traditional plain concrete has obvious deficiencies in waterproof performance. Due to the tiny pores and cracks inside the concrete, water molecules can easily penetrate into the concrete through these channels, causing the deterioration and destruction of the concrete structure, affecting its use.
[0004] Therefore need to make a kind of clear water concrete with good waterproof effect. Summary of the invention
[0005] In order to improve the water resistance and compressive strength of plain concrete, the present application provides plain concrete and a preparation method thereof.
[0006] In the first aspect, the present application provides a kind of plain concrete, adopting the following technical scheme: A kind of plain concrete, comprising the following raw materials in parts by weight: 20-30 parts of cement, 35-41 parts of coarse aggregate, 28-32 parts of fine aggregate, 10-15 parts of water, 0.6-0.8 parts of water reducer, 3-5 parts of resin material, 5-7 parts of modified carbon nanotubes, 0.1-0.3 parts of defoamer, and 2-3 parts of polyamide-imide, wherein the modified carbon nanotubes are modified from alkoxysilane emulsion.
[0007] By adopting the above technical solution, the introduction of modified carbon nanotubes significantly improves the hydrophobicity of plain concrete. The modification of alkoxysilane emulsion makes the surface of carbon nanotubes have excellent hydrophobic properties. When these modified carbon nanotubes are evenly dispersed in concrete, they can form a dense hydrophobic barrier inside the concrete, effectively preventing the penetration and diffusion of water molecules and improving the anti-seepage performance of concrete.
[0008] Secondly, the addition of modified carbon nanotubes also significantly enhances the compressive strength of plain concrete. The modified carbon nanotubes have good interfacial bonding with the cement matrix, and they can play a reinforcing role in concrete like "rebars". When concrete is subjected to external forces, the modified carbon nanotubes can effectively transmit and disperse stress, preventing excessive cracks and damage inside the concrete. At the same time, the modified carbon nanotubes can also form a tight composite structure with other components in concrete, such as coarse aggregates and fine aggregates, further improving the overall strength of concrete.
[0009] In addition, the solution also adds resin materials, polyamide-imide and other components, which can work together with modified carbon nanotubes to form a more complex composite structure to disperse and offset the stress. The resin material has good adhesion and filling properties, which can fill the tiny pores and defects in the concrete and improve the density and compressive strength of the concrete.
[0010] Optionally, the modified carbon nanotubes include the following raw materials in parts by weight: 12-15 parts of alkoxysilane emulsion, 8-10 parts of Carbon nanotubes, 2-2.5 parts of ethylenediamine, and 1-2 parts of 4-dimethylaminopyridine.
[0011] By adopting the above technical solution, the introduction of organic silicon compounds through alkoxysilane can improve the compatibility and dispersibility of carbon nanotubes with concrete substrates, which helps to improve the compressive strength of concrete.
[0012] Optionally, the modified carbon nanotubes include the following preparation steps: (1) pre-treating the carbon nanotubes by soaking them in a strong acid, and then centrifuging and filtering them to obtain the acidified carbon nanotubes; (2) At 50-70°C, 4-dimethylaminopyridine is used as a catalyst, the acidified carbon nanotubes are dispersed in toluene, ethylenediamine is added and stirred for 2-4 hours, and then washed with anhydrous ethanol and dried to obtain amino-modified carbon nanotubes; (3) The amino-modified carbon nanotubes prepared above are placed in an ionic liquid and stirred to mix well, an alkoxysilane emulsion is added, and the mixture is stirred and reacted at 80-100° C. for 8-10 hours, and then filtered and dried to obtain the modified carbon nanotubes.
[0013] By adopting the above technical scheme, the carbon nanotubes are modified so that silane molecules are grafted on the surface of the carbon nanotubes. On the one hand, the dispersibility and compatibility of the carbon nanotubes in concrete can be improved. On the other hand, the good water resistance of the silane molecules makes it more resistant to stains, keeps the surface of the plain concrete clean and smooth, and improves the overall aesthetics of the building.
[0014] Furthermore, the silane molecules grafted on the carbon nanotubes form silanamine compounds that react with cement in concrete to form calcium silicate colloids, filling the pores in the concrete and enhancing the compactness of the concrete, thereby improving the compressive strength of the concrete. At the same time, the carbon nanotubes carrying silanamine compounds are oriented on the surface of the concrete, cross-linked and cured to form a hydrophobic surface layer, effectively blocking the penetration of water, and further improving the water resistance and stain resistance of the concrete.
[0015] Optionally, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate.
[0016] By adopting the above technical solution, 1-butyl-3-methylimidazolium hexafluorophosphate has excellent solubility and dispersion properties, and can effectively dissolve and disperse amino-modified carbon nanotubes. This ability enables BMIMPF6 to promote the full contact and reaction between carbon nanotubes and alkoxysilane emulsion during the reaction process, while achieving efficient reaction and reducing the occurrence of agglomeration and precipitation. At the same time, its catalytic effect can achieve the modification of carbon nanotubes under milder conditions.
[0017] Optionally, the resin material is epoxy resin.
[0018] By adopting the above technical scheme, the epoxy resin itself has good water resistance and can form a dense waterproof layer inside the concrete, reduce the water absorption and penetration inside the concrete, and improve the waterproof performance of the concrete. At the same time, the epoxy resin can be mixed with the polyamide-imide to cross-link and solidify to form a cross-linked network. This cross-linked network structure has excellent mechanical properties and stability, further improving the compressive strength of the concrete. At the same time, the bonding effect of the epoxy resin can also enhance the connection between the components inside the concrete, further improving the overall strength of the concrete.
[0019] Optionally, the defoaming agent is naphthalenesulfonic acid formaldehyde condensate sodium salt.
[0020] By adopting the above technical solution, the naphthalenesulfonic acid formaldehyde condensate is a polar molecule, in which the sulfonic acid group is a strong hydrophilic group, which enables it to be effectively dispersed in the water phase and quickly reduce the number of bubbles in the concrete. At the same time, it does not generate gas during the defoaming process, which prevents the introduction of gas during the preparation of concrete, resulting in bubbles on the surface of the concrete after subsequent curing, affecting the strength and appearance of the concrete. In addition, the sulfonic acid group on it can react with the modified carbon nanotubes, further serving as a dispersant and stabilizer for the modified carbon nanotubes, and improving the performance of the concrete.
[0021] Optionally, the raw materials also include 3-4 parts of perfluorotripropylamine.
[0022] By adopting the above technical solution, perfluorotripropylamine is used as an inert solution, and the fluorine element provided thereon reduces the free energy of the concrete surface, making it difficult for moisture to adhere to and penetrate the surface, thereby further improving the water resistance of the concrete.
[0023] In a second aspect, the present application provides a method for preparing plain concrete, which adopts the following technical solution: A method for preparing plain concrete comprises the following steps: The modified carbon nanotubes, coarse aggregate, fine aggregate and cement are mixed and stirred evenly, and water is added. During the mixing process, a water reducing agent, a resin material, polyamide-imide and a defoaming agent are added and mixed evenly to obtain the plain concrete.
[0024] In summary, this application has the following beneficial effects: 1. Since the present application introduces modified carbon nanotubes modified by alkoxysilane emulsion, the impermeability and compressive strength of plain concrete are significantly improved. The modified carbon nanotubes form a dense hydrophobic barrier inside the concrete, effectively preventing the penetration and diffusion of water molecules. At the same time, the modified carbon nanotubes have good interfacial bonding with the cement matrix, which can enhance the compressive strength of concrete like "rebar". In addition, the combined action with components such as resin materials and polyamide-imide further forms a complex composite structure, which improves the overall strength of the concrete.
[0025] 2. In the present application, epoxy resin, polyamide-imide and modified carbon nanotubes cooperate with each other to produce a thin film with a hydrophobic effect in concrete, thereby effectively reducing the surface tension of concrete, reducing bubble formation, and improving the aesthetics of plain concrete.
[0026] 3. The formula uses sodium salt of naphthalenesulfonic acid formaldehyde condensate as a defoamer. Its polar molecular structure and strong hydrophilic group enable it to be effectively dispersed in the water phase, quickly reducing the number of bubbles in the concrete, and avoiding the appearance of bubbles on the concrete surface after subsequent curing due to the introduction of gas, which affects the strength and appearance of the concrete. In addition, perfluorotripropylamine is added to the formula. The fluorine element it provides reduces the free energy of the concrete surface, making it difficult for water to adhere to and penetrate the surface, improving the water resistance of the concrete, and further improving the appearance of the concrete. DETAILED DESCRIPTION
[0027] The present application is further described in detail below with reference to the embodiments.
[0028] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0029] The coarse aggregate is a mixture of crushed stone with a particle size of 5mm-10mm and a particle size of 10mm-20mm in a mass ratio of 3:17; the fine aggregate is a fineness modulus of 2.5, a mud content of 0.6%, and a bulk density of 1550kg / m 3 The machine-made sand is made of; the water reducer is polycarboxylic acid water reducer; the polyamide-imide is purchased from Shanghai Beidaer New Materials Co., Ltd., model: 4200; the cement is silicate cement purchased from Sanhe Yanhong Trading Co., Ltd., item number ZP-001; the polyether defoamer is purchased from Jining Youshun New Materials Co., Ltd., model YS-001; the epoxy resin is purchased from Langfang Nanze Anticorrosion Materials Co., Ltd., brand E-44.
[0030] Preparation examples of raw materials and / or intermediates Preparation Example 1 A modified carbon nanotube, the preparation of which comprises the following steps: (1) adding 10 kg of carbon nanotubes into a mixed acid of sulfuric acid and nitric acid in a ratio of 3:1, immersing in an ultrasonic bath for 1 h, and centrifuging and filtering to obtain acidified carbon nanotubes; (2) In a 60° C. water bath, the acidified carbon nanotubes obtained above were dispersed in 20 kg of toluene, 1 kg of 4-dimethylaminopyridine was added as a catalyst, 2.5 kg of ethylenediamine was added and stirred continuously for 4 h, and then washed with anhydrous ethanol for 3-4 times, and vacuum dried at 60° C. to obtain amino-modified carbon nanotubes; (3) The amino-modified carbon nanotubes prepared above were placed in 16 kg of 1-butyl-3-methylimidazolium hexafluorophosphate ionic liquid and stirred to mix well. 15 kg of 3-aminopropyltriethoxysilane emulsion (alkoxysilane emulsion) was added and stirred at 80° C. for 10 hours, and then filtered and dried to obtain the modified carbon nanotubes.
[0031] Preparation Example 2 A modified carbon nanotube, the preparation of which comprises the following steps: (1) adding 9 kg of carbon nanotubes into a mixed acid of sulfuric acid and nitric acid in a ratio of 3:1, immersing in an ultrasonic bath for 1 h, and centrifuging and filtering to obtain acidified carbon nanotubes; (2) In a 50° C. water bath, the acidified carbon nanotubes obtained above were dispersed in 20 kg of toluene, 1.5 kg of 4-dimethylaminopyridine was added as a catalyst, and 2 kg of ethylenediamine was added and stirred for 2 h, and then washed with anhydrous ethanol for 3-4 times, and vacuum dried at 60° C. to obtain amino-modified carbon nanotubes; (3) The amino-modified carbon nanotubes prepared above were placed in 16 kg of 1-butyl-3-methylimidazolium hexafluorophosphate ionic liquid and stirred to mix well. 12 kg of 3-aminopropyltriethoxysilane emulsion (alkoxysilane emulsion) was added and stirred for reaction at 100° C. for 8 h, and then filtered and dried to obtain the modified carbon nanotubes.
[0032] Preparation Example 3 A modified carbon nanotube, the preparation of which comprises the following steps: (1) adding 8 kg of carbon nanotubes into a mixed acid of sulfuric acid and nitric acid in a ratio of 3:1, immersing in an ultrasonic bath for 1 h, and centrifuging and filtering to obtain acidified carbon nanotubes; (2) In a 70° C. water bath, the acidified carbon nanotubes obtained above were dispersed in 20 kg of toluene, 2 kg of 4-dimethylaminopyridine was added as a catalyst, 2.25 kg of ethylenediamine was added and stirred for 3 h, and then washed with anhydrous ethanol for 3-4 times, and vacuum dried at 60° C. to obtain amino-modified carbon nanotubes; (3) The amino-modified carbon nanotubes prepared above were placed in 16 kg of 1-butyl-3-methylimidazolium hexafluorophosphate ionic liquid and stirred to mix well. 13.5 kg of 3-aminopropyltriethoxysilane emulsion (alkoxysilane emulsion) was added and stirred at 90° C. for 9 h, and then filtered and dried to obtain the modified carbon nanotubes.
[0033] Preparation Example 4 A modified carbon nanotube, which is different from Preparation Example 1 in that the ionic liquid used in this Preparation Example is 1-butyl-3-methylimidazolium chloride. Example
[0034] Example 1 A kind of plain concrete, the preparation comprises the following steps: 6 kg of modified carbon nanotubes, 38 kg of coarse aggregate, 28 kg of fine aggregate and 30 kg of cement were mixed and stirred evenly, and 15 kg of water was added. During the mixing process, 0.7 kg of water reducer, 5 kg of epoxy resin, 3 kg of polyamide-imide and 0.2 kg of sodium salt of naphthalenesulfonic acid formaldehyde condensate (defoaming agent) were added and mixed evenly to obtain the plain concrete. The modified carbon nanotubes prepared in Preparation Example 1 were used in this application.
[0035] Example 2 A kind of plain concrete, the preparation comprises the following steps: 5 kg of modified carbon nanotubes, 35 kg of coarse aggregate, 32 kg of fine aggregate and 25 kg of cement were mixed and stirred evenly, and 10 kg of water was added. During the mixing process, 0.6 kg of water reducer, 4 kg of epoxy resin, 2 kg of polyamide-imide and 0.3 kg of sodium salt of naphthalenesulfonic acid formaldehyde condensate (defoaming agent) were added and mixed evenly to obtain the plain concrete. The modified carbon nanotubes prepared in Preparation Example 1 were used in this application.
[0036] Example 3 A kind of plain concrete, the preparation comprises the following steps: 7 kg of modified carbon nanotubes, 41 kg of coarse aggregate, 30 kg of fine aggregate and 20 kg of cement were mixed and stirred evenly, and 12.5 kg of water was added. During the mixing process, 0.8 kg of water reducer, 3 kg of epoxy resin, 2.5 kg of polyamide-imide and 0.1 kg of sodium salt of naphthalenesulfonic acid formaldehyde condensate (defoaming agent) were added and mixed evenly to obtain the plain concrete. The modified carbon nanotubes prepared in Preparation Example 1 were used in this application.
[0037] Example 4 A plain concrete, which is different from Example 1 in that the modified carbon nanotubes prepared in Preparation Example 2 are used in this example.
[0038] Example 5 A plain concrete, which is different from Example 1 in that the modified carbon nanotubes prepared in Preparation Example 3 are used in this example.
[0039] Example 6 A plain concrete, which is different from Example 1 in that the modified carbon nanotubes prepared in Preparation Example 4 are used in this example.
[0040] Example 7 A kind of plain concrete, which is different from the embodiment 1 in that the resin material used in the embodiment is polyurethane resin.
[0041] Example 8 A kind of plain concrete, which is different from Example 1 in that the defoamer used in this example is a polyether defoamer.
[0042] Example 9 A plain concrete, which is different from Example 1 in that this embodiment further includes 3 kg of perfluorotripropylamine.
[0043] Example 10 A plain concrete, which is different from Example 1 in that this embodiment further includes 4 kg of perfluorotripropylamine.
[0044] Comparative Example Comparative Example 1 A plain concrete, which is different from Example 1 in that the carbon nanotubes added in this comparative example are not modified.
[0045] Comparative Example 2 A kind of plain concrete, which is different from Example 1 in that epoxy resin is not added in this comparative example.
[0046] Comparative Example 3 A kind of plain concrete, which is different from Example 1 in that polyamide-imide is not added in this comparative example.
[0047] Performance testing Detection method / test method Compressive strength test: GB / T50081-2002 "Standard for Experimental Methods of Mechanical Properties of Ordinary Concrete" tests the mechanical properties of concrete prepared in the examples and comparative examples. The specific results are shown in Table 1; Water penetration resistance: Water penetration resistance test: According to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the prepared concrete was tested for water penetration resistance using the water seepage height method. The curing age was 28 days. A truncated cone with a diameter of 175 mm, an inner diameter of 185 mm at the lower mouth and a height of 150 mm was used for the test. A rubber sealing ring was used as the sealing material. The specimen was taken out 24 hours before the test age was reached. The specimen was sealed with a rubber sealing ring. According to the specifications, 1.2±0.05 MPa was selected as the constant water pressure within 24 hours. A concrete impermeability meter was used as the test instrument to determine the average water seepage height of different impermeable concretes under constant water pressure.
[0048] Table 1 Test results Compressive strength / MPa Water seepage height / mm Example 1 49.12 1.75 Example 2 48.89 1.78 Example 3 48.67 1.77 Example 4 48.54 1.91 Example 5 48.32 1.89 Example 6 48.78 1.85 Example 7 45.34 2.26 Example 8 46.98 2.18 Example 9 50.23 1.54 Example 10 51.01 1.49 Comparative Example 1 40.23 4.12 Comparative Example 2 43.56 3.27 Comparative Example 3 42.28 3.63 Combining Examples 1-3 and Comparative Example 1 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 1, indicating that further modification of carbon nanotubes with alkoxysilane emulsion can improve the dispersibility and compatibility of carbon nanotubes in concrete, thereby improving the reinforcement effect of carbon nanotubes on concrete, enabling it to have higher compressive strength, and the modification gives carbon nanotubes good waterproof properties. The functional groups introduced can interact with the raw materials in concrete to further fill the pores in the concrete and improve the compressive strength of the concrete.
[0049] Combining Examples 1-3, Comparative Example 2, Example 7 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Example 7, and the experimental data of Example 7 are better than those of Comparative Example 2, indicating that the addition of resin materials can synergistically improve the various properties of concrete with other components in the raw materials, and in particular, the addition of epoxy resin can further enhance the waterproof and dirt penetration capabilities of concrete, and it interacts with raw materials such as polyamide-imide in the raw materials to form a cross-linked network, thereby enhancing the compressive strength of concrete.
[0050] Combining Examples 1-3 and Comparative Example 3 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 3, indicating that polyamide-imide can interact with the resin material in the raw material and the modified carbon nanotubes to form a compact hydrophobic network structure, effectively preventing the penetration of moisture and dirt. At the same time, its excellent mechanical properties also greatly improve the ultimate compressive strength of the concrete.
[0051] It can be seen from Examples 1-6 and Table 1 that the test data of Examples 1-5 are better than those of Example 6, indicating that the use of 1-butyl-3-methylimidazolium hexafluorophosphate as an ionic liquid can improve the modification effect on carbon nanotubes, and can interact with the functional groups on the carbon nanotubes to achieve the modification of the carbon nanotubes, thereby further improving the waterproof performance of concrete and improving the compressive strength of concrete.
[0052] Combining Example 1 with Example 8 and Table 1, it can be seen that the various test data of Example 1 are better than those of Example 8, indicating that the selection of the defoamer affects the final performance of the concrete. The selection of the sodium salt of naphthalenesulfonic acid formaldehyde condensate defoamer can improve the dispersibility and stability of the modified carbon nanotubes while eliminating bubbles and improving the compressive properties and aesthetic properties of the concrete, thereby further improving the compressive strength and water resistance of the concrete.
[0053] Combining Example 1 with Examples 9-10 and Table 1, it can be seen that the test data of Examples 9-10 are better than those of Example 1, indicating that the addition of perfluorotripropylamine can help reduce the surface energy of concrete and help improve the waterproof ability of concrete.
[0054] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A kind of plain concrete, characterized in that: The composition comprises the following raw materials in parts by weight: 20-30 parts of cement, 35-41 parts of coarse aggregate, 28-32 parts of fine aggregate, 10-15 parts of water, 0.6-0.8 parts of water reducer, 3-5 parts of resin material, 5-7 parts of modified carbon nanotubes, 0.1-0.3 parts of defoamer, and 2-3 parts of polyamide-imide, wherein the modified carbon nanotubes are modified from alkoxysilane emulsion.
2. The plain concrete according to claim 1, characterized in that: The modified carbon nanotube comprises the following raw materials in parts by weight: 12-15 parts of alkoxysilane emulsion, 8-10 parts of carbon nanotube, 2-2.5 parts of ethylenediamine and 1-2 parts of 4-dimethylaminopyridine.
3. The plain concrete according to claim 2, characterized in that: The modified carbon nanotubes include the following preparation steps: (1) pre-treating the carbon nanotubes by soaking them in a strong acid, and centrifuging and filtering them to obtain the acidified carbon nanotubes; (2) At 50-70°C, 4-dimethylaminopyridine is used as a catalyst, the acidified carbon nanotubes are dispersed in toluene, ethylenediamine is added and stirred for 2-4 hours, and then washed with anhydrous ethanol and dried to obtain amino-modified carbon nanotubes; (3) The amino-modified carbon nanotubes prepared above are placed in an ionic liquid and stirred to mix well, an alkoxysilane emulsion is added, the mixture is stirred and reacted at 80-100° C. for 8-10 hours, and then filtered and dried to obtain the modified carbon nanotubes.
4. The plain concrete according to claim 1, characterized in that: The ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate.
5. The plain concrete according to claim 1, characterized in that: The resin material is epoxy resin.
6. The plain concrete according to claim 1, characterized in that: The defoamer is naphthalenesulfonic acid formaldehyde condensate sodium salt.
7. The plain concrete according to claim 1, characterized in that: The raw materials also include 3-4 parts of perfluorotripropylamine.
8. A method for preparing a plain concrete according to any one of claims 1 to 6, characterized in that: The steps include: The modified carbon nanotubes, coarse aggregate, fine aggregate and cement are mixed and stirred evenly, and water is added. During the mixing process, a water reducing agent, a resin material, polyamide-imide and a defoaming agent are added and mixed evenly to obtain the plain concrete.